Design and preparation of efficient hydroisomerization catalysts by the formation of stable SAPO-11 molecular sieve nanosheets with 10–20 nm thickness and partially blocked acidic sites. Issue 36 (19th April 2017) - Zhang, Fen; Liu, Yan; Sun, Qi; Dai, Zhifeng; Gies, Hermann; Wu, Qinming; Pan, Shuxiang; Bian, Chaoqun; Tian, Zhijian; Meng, Xiangju; Zhang, Yi; Zou, Xiaodong; et al.
Abstract : Stable SAPO-11 nanosheets (10–20 nm thickness) with partially blocked acidity are successfully prepared. Abstract : SAPO-11 nanosheets with partially filled micropores (N-SAPO-11) and a thickness of 10–20 nm were synthesized using polyhexamethylene biguanide hydrochloride (PHMB) as a mesoporogen and di- n -propylamine (DPA) as a microporous template. After Pt loading (0.5 wt%), the Pt/N-SAPO-11 catalyst exhibits higher selectivity for the isomers and lower selectivity for cracking products than conventional Pt/SAPO-11 catalysts in the hydroisomerization of n -dodecane.